Are There Differences in the Progression of Ossification of the Posterior Longitudinal Ligament Following Laminoplasty Versus Fusion?: A Meta-Analysis. Issue 12 (15th June 2017) - Lee, Chang-Hyun; Sohn, Moon-Jun; Lee, Chae Heuck; Choi, Chan Young; Han, Seong Rok; Choi, Byung-Wan
Abstract : Study Design: Systematic review and meta-analysis of studies for the treatment of cervical myelopathy with ossification of the posterior longitudinal ligament (OPLL) treated with laminoplasty or fusion. Objective: To delineate whether OPLL continues to progress after laminoplasty compared with fusion and to clarify the relationship between radiological progression of OPLL and neurological decline. Summary of Background Data: Laminoplasty is usually performed in patients with multilevel OPLL due to the surgical morbidity of anterior surgery. However, the disadvantage of laminoplasty is that the remaining OPLL can progress after the surgery. Methods: A literature search of PubMed, Embase, Web of Science, and the Cochrane library was performed to identify investigations concerning the progression of OPLL after laminoplasty or fusion. The pooled results were analyzed by calculating the effect size based on the event rate and the logit event rate. Results: We included data from 11 studies involving 530 patients, of whom 429 underwent laminoplasty and 101 underwent fusion surgery. The prevalence of radiological OPLL progression was 62.5% (95% confidence interval [CI] 55.3%–69.3%) for the laminoplasty group and 7.6% (95% CI 3.4%–15.9%) for the fusion group. The laminoplasty displayed substantially high prevalence of the progression of OPLL compared with the fusion group. In the laminoplasty group, the prevalence of OPLL progression increased with time and reached 60% at about 10-year follow-up. The prevalence for neurological decline was similar for about 2 years, 8.3% (95% CI 3.7%–17.9%) for the laminoplasty group and 3.8% (95% CI 1.3%–10.2%) for the fusion group. Conclusion: Laminoplasty frequently induces progression of OPLL compared with fusion surgery, but does not make significant clinical deterioration. However, laminoplasty may not be recommended for OPLL patient because it can be getting worse with time. Level of Evidence: 1